PENGEMBANGAN MEDIA PERMAINAN ULAR TANGGA UNTUK PENINGKATKAN KETERAMPILAN BERFIKIR SISWA DALAM MATERI MAJAS METAFORA - Najikhah, Fatikhatun; Masfuah, Siti; Fatimah, Siti; Anggraini, Ririn; Setyaningsih, Mawar (Universitas Negeri Medan, 2024)
Abstract: This research aims to develop the metaphorical snakes and ladders game media, how valid and practical the metaphorical snakes and ladders game media is and to find out how to improve students' thinking skills in using the metaphorical snakes and ladders metaphorical game media. The research method used is the development type which is a limited scale trial stage of Research and Development. The subjects studied were Class IV students at SDN 3 Bulungkulon. Data collection techniques use observation sheets, interviews, questionnaires, validation sheets, and thinking ability tests. The research results showed that 95% of the results of the validation questionnaire were valid, the student response questionnaire was 3.3, which means very good, and student learning outcomes increased by 13% after testing the metaphorical figurative snake and ladder game media. This shows that there is an increase in students' thinking skills after using the metaphorical figure of speech snake and ladder game media.Keyword: Snakes and Ladders Media, Metaphors, Thinking SkillsAbstrak: Penelitian ini bertujuan untuk mengembangkan media permainan ular tangga majas metafora bagaimana kevalidan dan kepraktisan media permainan ular tangga majas metafora serta mengetahui peningkatan keterampilan berfikir siswa dalam menggunakan media permainan ular tangga majas metafora. Metode penelitian yang digunakan yaitu jenis pengembangan yang merupakan tahap uji coba skala terbatas dari Research and Development.. Subjek yang diteliti adalah siswa Kelas IV SDN 3 Bulungkulon. Tehnik pengumpulan data menggunakan lembar observasi, wawancara, angket, lembar validasi, dan tes kemampuana berfikir. Hasil penelitian menunjukkan 95% dari hasil angket validasi, angket respon peserta didik sebesar 3,3 yang berarti baik sekali dan hasil belajar siswa yang mengalami peningkatan sebesar 13% sesudah uji coba media permainan ulartangga majas metafora. Hal ini menunjukan bahwa terjadi peningkatan keterampilan berfikir siswa setelah menggunakan media permainan ulartangga majas metafora.Kata Kunci: Media Ular Tangga, Majas Metafora, Keterampilan Befikir